Impact of tablets on learning and perceptions of the indigenous educational community of Amazonas - Guevara-Goñas, Roger Ercilio; Tongo-Alarcon, Delmar; Ayay-Arista, Guido; Cuja-Quiac, Sebanias (Journal of Education and e-Learning Research, 2025)
The objective of this research was to evaluate the impact of tablets on the learning of indigenous students in the department of Amazonas and to analyze the perceptions of educational subjects regarding the pedagogical use of these technological tools. A quantitative-descriptive approach was used employing standardized tests and perception surveys. The population consisted of 2,342 students whose learning was assessed and 180 respondents, including teachers, parents, and indigenous students. The results showed that 82% of students were at the lowest learning levels with only 4.7% achieving a satisfactory level. 54.65% of teachers had never used tablets for pedagogical purposes due to a lack of training (84.84%) and connectivity (55.10%). Regarding parents, 49.80% stated that these tools were never used for educational purposes. 59.72% of students responded that they had never used tablets at home for educational purposes. The conclusion is that connectivity limitations and a lack of training have led to a low impact on learning and negative perceptions in the educational community. Thus, the need to implement comprehensive strategies for training, connectivity and the provision of technological resources to improve the education of indigenous students is underscored.